LEGAL PROTECTION OF CHILDREN'S RIGHTS IN HIGHER EDUCATION ENVIRONMENTS: A CASE STUDY OF INDONESIA AND MALAYSIA - Rahul Ardian Fikri; Irma Fatmawati; Moses Elias Perangin-Angin (RADJA PUBLIKA, 2025)
Demographic shifts in higher education have led to an increase in the number of students under 18, triggering uncertainty about their legal status and the urgency of special protections. This normative legal research comparatively analyzes the regulatory frameworks and institutional mechanisms for student protection in Indonesia and Malaysia. Through a legislative and comparative approach, the study finds divergences in the characteristics of protection. Indonesia implements a structural-administrative model through the PPK Task Force based on Ministerial Regulation No. 55 of 2024, which prioritizes internal prevention and broad coverage, but is hampered by structural independence. In contrast, Malaysia adopts a remedial-legalistic model through the Anti-Sexual Harassment Tribunal Act 2022, which offers executive certainty and independence, but is materially limited to sexual offenses and is reactive in nature. The research concludes that both jurisdictions need to harmonize towards a hybrid model. Indonesia is recommended to establish an external oversight mechanism to mitigate conflicts of interest, while Malaysia needs to integrate a mandatory prevention curriculum and expand protections against bullying. The direction of legal policy is expected to shift from rigid age limits to vulnerability-based protection that is responsive to power relations in the academic environment.